“Fulfilled by Amazon”: A Strategic Perspective of Competition at the e-Commerce Platform - Lai, Guoming; Liu, Huihui; Xiao, Wenqiang; Zhao, Xinyi (Manufacturing and Service Operations Management, 2022)
Problem definition: This paper examines the economic effects of the fulfillment services offered by Amazon (FBA) to the third-party sellers on its retail platform. Academic/practical relevance: Logistics is critical for e-commerce. It is intriguing that the third-party sellers that use FBA may directly compete with Amazon. By FBA, their service levels are substantially improved and so is their competitiveness. Such a phenomenon has been little investigated in prior literature. Methodology: We develop a strategic competition model where Amazon and a representative third-party seller engage in both price and service competition. Results: Interestingly, we find that although FBA may intensify the service competition between Amazon and the third-party seller, it can mitigate their price competition besides the direct revenue Amazon collects from the service. The latter effects dominate the former when the cross-service sensitivity of the consumers is either sufficiently low or sufficiently high. Therefore, not only the third-party sellers but also Amazon may benefit from FBA. Moreover, because the sales of Amazon’s products may increase because of FBA, its OEM (original equipment manufacturer) supplier may gain from FBA also. These findings extend to the settings where the third-party seller is Amazon’s OEM supplier, cross-price and cross-service sensitivities are correlated, or the parties set their retail prices sequentially. Managerial implications: Our analysis provides insights about when FBA is more likely to be beneficial and when it can be harmful. They are useful for understanding the impacts of FBA on both Amazon and the third-party sellers.